2016
DOI: 10.1007/s00428-016-1914-0
|View full text |Cite
|
Sign up to set email alerts
|

A high number of IgG4-positive cells in gastric cancer tissue is associated with tumor progression and poor prognosis

Abstract: IgG4-related disease is a newly defined disease characterized by elevated serum IgG4 levels and infiltration of affected organs by IgG4-positive plasma cells. Recently, increased IgG4 levels were reported to be closely related with malignancy. To assess the relationship between IgG4 and the progression of gastric cancer, we immunohistochemically stained in this study gastric cancer tissue samples for IgG4-positive cells using an anti-IgG4 antibody. In addition, pre- and postoperative serum concentrations of Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Neoplastic conditions associated with IgG4 + PCs have been reported in sclerosing mucoepidermoid carcinoma of the salivary gland [14,15], non-small-cell lung cancers [16], extrahepatic cholangiocarcinoma [17], gastric cancer [18] and Warthin tumor [19]. The exact prevalence and nature of this phenomenon are still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic conditions associated with IgG4 + PCs have been reported in sclerosing mucoepidermoid carcinoma of the salivary gland [14,15], non-small-cell lung cancers [16], extrahepatic cholangiocarcinoma [17], gastric cancer [18] and Warthin tumor [19]. The exact prevalence and nature of this phenomenon are still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4 þ PC are associated with fibroinflammatory disease and may play an immunosuppressive role in cancer (61). Accordingly, IgG4 þ cells were found to have a negative prognostic effect in gastric cancer (62) and PDAC (63), but were not prognostic in NSCLC (16). Bosisio and colleagues found that IgA þ CD138 þ TIL were associated with poor prognosis in melanoma (58), which was opposite to the results reported when CD138 was used as a single marker in this setting (43).…”
Section: Plasma Cellsmentioning
confidence: 98%
“…Immunofluorescence staining for PD-1 and CD68 was performed as previously described [15]. Four μm thick paraffinembedded sections were incubated with primary antibodies, which were the same antibodies used in immunohistochemistry, overnight at 4°C.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%